Hubungan Perubahan Kualitas Air Dan Pertumbuhan Fitoplankton Berbahaya Pada Lingkungan Budidaya Ikan Di Perairan Ringgung Teluk Lampung - Agus Solihin; Qadar Hasani; Herman Yulianto (AQUASAINS, 2015)
Water quality becomes the critical factor of successfully aqua culture process; especially this is in aquaculture of floating cages. Otherwise, unstable water quality could impact the negative effect toward aquatic ecosystem such as the large explosion of harmful phytoplankton population (HABs). The objective of this research is to analyze a relation between the water quality of floating cages and the growth of harmful phytoplankton population by using canocial corelation analysis. Water quality research includes its brightness, the deepness, disolved oxygen, salinity, pH, value of NO2, NO3, NH3, and PO4 and toxic phytoplankton obtained during the study also indicate the amount of phytoplankton growth The results were obtained 14 species of toxic phytoplankton in the study sites. Overall abundance of phytoplankton dominated by Choclodinium, Trichodesmium Erythraeum, Nitzschia Lanceolata dan Pseudo Nitzschia, where Choclodinium an abundance of phytoplankton with the highest density of 63 739 cells/l. Canonical correlation analysis on triplot diagram showed water quality includes : brightness, disolved oxygen, pH, NO2, NO3 and PO4 together to give effect to toxic phytoplankton abundance. Canonical correlation analysis also specifically indicate the abundance Choclodinium and Trichodesmium Erythraeum in floating nets of Ringgung Marines predominantly influenced by brightness, pH, value of NO3, and PO4.